2020
DOI: 10.1007/s00415-020-10195-w
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the relative contribution of comorbidities in predicting health-related quality of life of people with multiple sclerosis

Abstract: Background:Little is known about the relative contribution of comorbidities in predicting the health-related quality of life (HRQoL) of people with Multiple Sclerosis (PwMS).Objective: To determine the associations between the number of and individual comorbidities and HRQoL and estimate the relative contribution of different comorbidities on HRQoL.Methods: Cross-sectional analysis of data on self-reported presence of 30 comorbidities and HRQoL from the Australian MS Longitudinal Study (AMSLS) participants(n=9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 27 publications
(38 reference statements)
1
30
0
Order By: Relevance
“…The sex distribution was 5605 female patients and 1902 male patients, and the mean age was 45.6 years. Among the methodologies, six studies were cross-sectional ( Kahraman et al, 2021 ; Kowalec et al, 2017 ; Lo, Taylor, Winzenberg, Palmer, Blizzard and van der Mei, 2021a ; Lo, Taylor, Winzenberg, Palmer, Blizzard, Ahmad, et al, 2021b ; Marrie et al, 2018b ; Viana et al, 2015 ), five were prospective cohort studies ( Fiest et al, 2016 ; Marrie, Zhang, et al, 2018a ; McKay et al, 2016 ; Whitehouse et al, 2019 ; Wicks et al, 2016 ) and one was a retrospective cohort study ( Lorefice et al, 2015 ) ( Table 1 ). It was observed that six studies were carried out in North America, two studies in Oceania and four studies in Europe ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sex distribution was 5605 female patients and 1902 male patients, and the mean age was 45.6 years. Among the methodologies, six studies were cross-sectional ( Kahraman et al, 2021 ; Kowalec et al, 2017 ; Lo, Taylor, Winzenberg, Palmer, Blizzard and van der Mei, 2021a ; Lo, Taylor, Winzenberg, Palmer, Blizzard, Ahmad, et al, 2021b ; Marrie et al, 2018b ; Viana et al, 2015 ), five were prospective cohort studies ( Fiest et al, 2016 ; Marrie, Zhang, et al, 2018a ; McKay et al, 2016 ; Whitehouse et al, 2019 ; Wicks et al, 2016 ) and one was a retrospective cohort study ( Lorefice et al, 2015 ) ( Table 1 ). It was observed that six studies were carried out in North America, two studies in Oceania and four studies in Europe ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… Cross-sectional study; No mention of age at MS symptom onset. 7 Lo et al (2021a) MS patients (N = 1518, 55.7 ± 11.3 years, F 1204, M 309) Cross-sectional Australia, Oceania. Treatment: (N = 947); PMS: (N = 150), RRMS: (N = 1113), Unknow: (N = 255); Age at MS symptom onset: 36.0 ± 10.8 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health disorders and musculoskeletal disorders had the largest relative contributions to the severity of common symptoms in MS. Interestingly, a companion paper in this issue shows that both mental health and musculoskeletal disorders were also the strongest contributors to lowering the health-related quality of life in people with MS in this same cohort. 25 Mental health disorders (with a diagnosis of depression having the largest individual contribution) had the largest relative contribution to the severity of feelings of anxiety, feelings of depression, cognitive symptoms, sensory symptoms, fatigue and sexual dysfunction. Musculoskeletal disorders (with osteoporosis having the largest individual contribution) had the largest relative contribution to the severity of pain, walking difficulties, difficulty with balance, bladder problems, bowel problems and spasticity.…”
Section: Discussionmentioning
confidence: 99%
“… 1 A previous study reported that the quality of a patient’s life was significantly lower than the control group using a SF-36 health questionnaire. 2 The functional damage of patients is gradually aggravated over the prolongation of time. 3 However, the specific pathological mechanism of SSc and its etiological factors remain unclear.…”
Section: Introductionmentioning
confidence: 99%